2010
DOI: 10.1093/jxb/erq090
|View full text |Cite
|
Sign up to set email alerts
|

To what extent may changes in the root system architecture of Arabidopsis thaliana grown under contrasted homogenous nitrogen regimes be explained by changes in carbon supply? A modelling approach

Abstract: Root system architecture adapts to low nitrogen (N) nutrition. Some adaptations may be mediated by modifications of carbon (C) fluxes. The objective of this study was to test the hypothesis that changes in root system architecture under different N regimes may be accounted for by using simple hypotheses of C allocation within the root system of Arabidopsis thaliana. With that purpose, a model during vegetative growth was developed that predicted the main traits of root system architecture (total root length, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, the important differences between these two experiments are the N stress regimes and durations of the N stress. In higher plants, different physiological responses were found between N limitation and N-free treatments and among different N regimes in the root system (Remans et al, 2006;Brun et al, 2010) and in the photosynthesis system (Sun et al, 2002). Our system may provide some physiological insight into chronic LN stress, which frequently occurs for major crop plants.…”
Section: Validation Of the Known Ln-responsive Mirnas And Difference Between Ln And N-free Stressesmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the important differences between these two experiments are the N stress regimes and durations of the N stress. In higher plants, different physiological responses were found between N limitation and N-free treatments and among different N regimes in the root system (Remans et al, 2006;Brun et al, 2010) and in the photosynthesis system (Sun et al, 2002). Our system may provide some physiological insight into chronic LN stress, which frequently occurs for major crop plants.…”
Section: Validation Of the Known Ln-responsive Mirnas And Difference Between Ln And N-free Stressesmentioning
confidence: 92%
“…Comparative analysis of identified known miRNAs at LN by microarray (Xu et al, 2011) with identified miRNAs under N-free conditions by sequencing (Zhao et al, 2012) indicates that around two-thirds of them matched each other. In Arabidopsis, different physiological responses were found in the root system under N limitation and N-free conditions (Remans et al, 2006), among different N regimes (Brun et al, 2010) and also in the photosynthesis system (Sun et al, 2002). However, there is limited information available for identification of novel zma-miRNAs associated with LN stress through sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Models can test and validate biological hypotheses, and models can be inverted to determine the hidden parameters of a system (Dupuy et al, 2010). Models can also integrate complex environmental and developmental variables, including, for example, response to water and nutrient supply (Dunbabin et al, 2002;Draye et al, 2010), various phosphorus concentrations (Fang et al, 2009), root adaptation to low nitrogen soil under carbon flux modifications (Brun et al, 2010), and the formation of root cortical aerenchyma in response to soil nutrient status (Postma and Lynch, 2011). Software packages are also available to facilitate the (re)construction of root systems, such as SimRoot (Lynch et al, 1997).…”
Section: Using Mathematical Simulation and Modelingmentioning
confidence: 99%
“…This hypothesis is consistent with that of Brun et al . () on Arabidopsis thaliana , who showed that carbon flux modifications within the root system explained the major part of root system adaptation to nitrogen availability.…”
Section: Discussionmentioning
confidence: 99%